2017
DOI: 10.1111/cea.12863
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association study of peanut allergy reproduces association with amino acid polymorphisms in HLADRB1

Abstract: Genetic determinants for challenge-proven peanut allergy include alleles at the HLA-DRB1 locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
(44 reference statements)
3
42
1
Order By: Relevance
“…Apart from the Howell et al and Madore et al studies, three other studies reported an association with peanut allergy, but these associations did not survive multiple testing adjustment (Table ). These studies had smaller sample sizes in comparison with other studies which may have contributed to the lack of association.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Apart from the Howell et al and Madore et al studies, three other studies reported an association with peanut allergy, but these associations did not survive multiple testing adjustment (Table ). These studies had smaller sample sizes in comparison with other studies which may have contributed to the lack of association.…”
Section: Resultsmentioning
confidence: 93%
“…Six of the nine studies that investigated HLA found associations with broad allele groups. With the exception of Savilahti et al who focused on cow's milk allergy, the remaining five studies investigated HLA in relation to peanut allergy . Savilahti et al did not find any significant associations with cow's milk allergy for HLA class II DR and DQ haplotypes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Hirsch et al. have looked for an associated between the use of antibiotics in each life and the subsequent development of food and other allergies. They used routine data from a large integrated United States health system.…”
mentioning
confidence: 99%